Infrastructure Development by Public-Private Partnership in Indonesia: A Systematic Literature Review - Mandasari, Vera; Wahjyuni, Ersa Tri (UI Scholars Hub, 2019)
Research on Public Private Partnership (PPP) in Indonesia has emerged over the last decade due to the increased popularity of PPP as one of the financing scheme for infrastructure project. This study aims to determine the trend of the PPP research in Indonesia between the period of 2002 and 2019 and identify the research gap. Papers from three academic citation engine; Google scholars, Sinta and Garuda were selected based on the specific words relevant to PPP issues in Indonesia. A total of 107 papers from both international and national journals are analysed to discover few themes of the paper and analyse them based on the categories emerging from the themes. The analysis revealed that the quantity of the paper steadily increase from the period of 2015 and are still dominated by authors from engineering science background (41.12%). Road (20.47%) and Water Supply (16.54%) are the popular objects in the study, followed by airport (3.94%). In term of methodology, case study of a PPP project has been a popular methodology chosen by 31 papers (28.97%). Top three topics in the literature have discussed risk analysis of PPP project (22.43%), the implementation of PPP (22,43%) and the BOT scheme (13,08%). The study identifies the literature gap in the accounting issues and taxation issues respectively, as well as the social impact of the PPP projects. Research on the three issues will enrich our understanding about the PPP issues in Indonesia.